Comparison of Absorbable and Nonabsorbable Sutures in Columellar Incision Closure in Rhinoplasty and Their Effects to Postoperative Scar - Kilavuz, Ahmet Erdem; Bayram, Ali Alper; Serin, Gediz Murat (Facial Plastic Surgery, 2017)
Open technique septorhinoplasty (SRP) provides better surgical control and stronger anatomical assessment; however, one of its biggest disadvantages is postoperative columellar scar. In this study, the authos aimed to compare the absorbable polyglactin 910 (PG) (Vicryl Rapide 6/0; Ethicon Inc.) and nonabsorbable polypropylene (PP) (Prolene 6/0; Ethicon Inc.) suture materials and their effects on the postoperative columellar scar. In this study, 89 patients (61 females and 28 males) who underwent primary open technique SRP were included; 42 patients were included in the PP group and 47 were included in the PG group. Sutures were removed in PP group on 7th postoperative day. Sutures were left to be absorbed in the PG group. Columellar scar was assessed with visual analog scale (VAS) subjectively and with the modified Stony Brook Scar Evaluation Scale (SBSES) objectively in 6th postoperative month. SBSES results in PG and PP groups were 3.88 ± 0.80 and 3.67 ± 0.80, respectively. There was no statistical significance between the two groups (p = 0.352). VAS results in PG and PP groups were 8.04 ± 0.91 and 7.71 ± 0.85, respectively. There was no statistical significance between the two groups (p = 0.200). No postoperative wound infection was seen in either of the groups. PG delivers good postoperative results in columellar scar. We recommend using PG for columellar incision closure since it provides less discomfort and anxiety for the patient, and less office time for the surgeon during the suture removal.
Keywords: columellar scar; septorhinoplasty; absorbable suture